2018
DOI: 10.1039/c8ra01261j
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of urchin-like RuCu and hollow RuCuMo nanoparticles and preliminary insight to their formation process by cyclic voltammetry

Abstract: The urchin-like RuCu and hollow RuCuMo nanocrystals were synthesized by one-pot chemical reduction method. The formation process of these nanocrystals was traced by cyclic voltammetry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…First, previous study indicated that only Cu 2+ ions cannot be reduced by benzyl alcohol [40]. On the contrary, Ru nanoparticles are often obtained through the reduction of Ru 3+ ions by polyol [40][41][42]. In this work, the presence of the Pd nanoplates facilitates the reduction of Cu 2+ ions to Cu atoms prior to Ru precursor due to the well-known underpotential deposition (UPD) [43].…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…First, previous study indicated that only Cu 2+ ions cannot be reduced by benzyl alcohol [40]. On the contrary, Ru nanoparticles are often obtained through the reduction of Ru 3+ ions by polyol [40][41][42]. In this work, the presence of the Pd nanoplates facilitates the reduction of Cu 2+ ions to Cu atoms prior to Ru precursor due to the well-known underpotential deposition (UPD) [43].…”
Section: Resultsmentioning
confidence: 92%
“…For comparison, the introduction of Cu here results in the formation of the porous nanoplates, indicating the critical role of Cu. First, previous study indicated that only Cu 2+ ions cannot be reduced by benzyl alcohol [40]. On the contrary, Ru nanoparticles are often obtained through the reduction of Ru 3+ ions by polyol [40][41][42].…”
Section: Resultsmentioning
confidence: 99%